C♯ 2010 fundamentals I, II, and III - Deitel, Paul J. (LiveLessons., 2011)
"The professional programmer's Deitel® guide to C♯ 2010 and the powerful Microsoft® .NET 4 Framework For programmers with a background in C++, Java or other high-level, object-oriented languages, this LiveLesson applies the Deitel signature live-code approach to teaching programming and explores Microsoft's C♯ 2010 language and .NET 4 in depth. The LiveLesson is updated for Visual Studio® 2010 and C♯ 4, and presents C♯ concepts in the context of 200+ fully tested programs. Start with a concise introduction to C♯ fundamentals using an early classes and objects approach, then rapidly move on to more advanced topics, including multithreading, .NET 4, LINQ, WPF, ASP.NET 4, WCF web services and Silverlight®. Along the way you'll enjoy the Deitels' classic treatment of object-oriented programming. When you're finished, you'll be ready to build next-generation Windows applications, web applications and web services."--Resource description page.